The Influence Of Organizational Culture And Motivation On The Work Ethics Of Civil Servants At The Regional Inspectorate Of Kubu Raya Regency - Meisha Ayudinita Sari; Irfan Mahdi (UNIVED Press, 2025)
This study aims to identify the influence of Organizational Culture and Motivation on the work ethics of civil servants at the Regional Inspectorate of Kubu Raya Regency. The research employs an associative approach, with a saturated sampling technique. The sample consists of 39 employees working at the Regional Inspectorate of Kubu Raya Regency. Data analysis was conducted using multiple linear regression analysis with SPSS 25 software. The tests performed in this study include validity testing, reliability testing, normality testing, linearity testing, and multicollinearity testing. Hypothesis testing was conducted using the Simultaneous Test (F Test) and Partial Test (T Test). Based on the results of the hypothesis tests, both simultaneously (F test) and partially (T test), it can be concluded that both Organizational Culture and Motivation have a positive and significant influence on work ethics. Moreover, both Organizational Culture and Motivation independently have a positive and significant effect on work ethics.